2023
DOI: 10.1111/jdi.13982
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine monophosphate deaminase in the endoplasmic reticulum–mitochondria interface promotes mitochondrial Ca2+ overload in type 2 diabetes rat hearts

Abstract: Aims/Introduction We previously showed that upregulation of myocardial adenosine monophosphate deaminase (AMPD) is associated with pressure overload‐induced diastolic dysfunction in type 2 diabetes hearts. Here, we examined involvement of AMPD localized in the endoplasmic reticulum–mitochondria interface in mitochondrial Ca 2+ overload and its pathological significance. Materials and Methods We used type 2 diabetes Otsuka Long–Evans Tokushima … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Disruption of Ca 2+ homeostasis in the mitochondria results in Ca 2+ overload, which impairs mitochondrial function. For example, the upregulation of myocardial adenosine monophosphate deaminase (AMPD) promotes MAM formation, triggering mitochondrial Ca 2+ overload and cardiac dysfunction in type 2 diabetes [ 58 ]. However, this study revealed only a linear relationship between AMPD expression and mitochondrial Ca 2+ overload in MAM, without providing insight into the specific mechanism by which AMPD regulates Ca 2+ overload.…”
Section: Ca 2+ Overloadmentioning
confidence: 99%
“…Disruption of Ca 2+ homeostasis in the mitochondria results in Ca 2+ overload, which impairs mitochondrial function. For example, the upregulation of myocardial adenosine monophosphate deaminase (AMPD) promotes MAM formation, triggering mitochondrial Ca 2+ overload and cardiac dysfunction in type 2 diabetes [ 58 ]. However, this study revealed only a linear relationship between AMPD expression and mitochondrial Ca 2+ overload in MAM, without providing insight into the specific mechanism by which AMPD regulates Ca 2+ overload.…”
Section: Ca 2+ Overloadmentioning
confidence: 99%
“…Intriguingly, before pressure overload, the Ca 2+ retention capacity in MAM-containing crude mitochondria of OLETF was 21% lower than that of LETO. Moreover, in vitro transfection of FLAG-AMPD3 in cells promotes the formation of MAM, resulting in m Ca 2+ overload, mitochondrial dysfunction and impaired mitochondrial respiration ( 37 ).…”
Section: Role Of Mam In Cardiac Diseasementioning
confidence: 99%